Golgi scaffold protein PAQR3 as a candidate suppressor of gastric cardia adenocarcinoma via regulating TGF‐β/Smad pathway. Issue 9 (23rd July 2022) - Wu, Ying‐Li; Hong, Lian‐Lian; Ling, Zhe‐Nan; Hu, Xuan‐Yu; Liu, Zhu; Li, Pei; Ling, Zhi‐Qiang
Abstract: Objectives: To investigate the function of PAQR3 in gastric cardia adenocarcinoma (GCA) and understand the possible mechanism of PAQR3 in regulating epithelial–mesenchymal transition (EMT). Methods: We detected PAQR3 protein in 146 GCA tissues and paired normal adjacent tissues (PNTs) specimens using immunohistochemical analysis, and explored its clinical significance. The expression levels of PAQR3 protein in 20 GCA tissues, their paired PNTs, HGC27, SGC7901, and GES‐1 cells were analyzed by Western blot. Wild‐type PAQR3 was overexpressed in HGC27 cells. The effects of PAQR3 overexpression on the function of HGC27 cells and its underlying mechanisms were then analyzed through a series of cell and molecular biology experiments. Results: PAQR3 was significantly down‐regulated in GCA tissues when compared with paired PNTs ( p  < 0.0001). The expression level of PAQR3 in GCA tissues was significantly negatively correlated with Helicobacter pylori infection ( p  = 0.000), venous invasion ( p  = 0.000), invasion depth ( p  = 0.000), lymph node metastasis ( p  = 0.022), tumor stage ( p  = 0.000), and patient survival ( p  = 0.009). Downregulation of PAQR3 was highly correlated with increased EMT signature and activated TGF‐β/Smad pathway in GCA tissues. Overexpression of PAQR3 in HGC27 cells negatively regulates its cellular functions, such as cell proliferation and migration, and suppresses EMT. Mechanistically, overexpression of PAQR3 significantly down‐regulates the protein expression levels of TGF‐1, p‐Smad2, and p‐Smad3 in HGC27 cells. Conclusion: PAQR3 was significantly down‐regulated in GCA tissues, HGC27, and SGC7901 cells. PAQR3 significantly inhibits the proliferation, migration, and invasion of HGC27 cells. Mechanistically, PAQR3 can inhibit the EMT process in HGC27 cells by regulating TGF‐β/Smad signaling pathway. Abstract : PAQR3 as a novel tumor suppressor gene can inhibit multiple tumorigenesis and development by regulating multiple signaling pathways, but whether PAQR3 can regulate TGF‐β signaling to influence the progression of GCA is unknown. In this study, we found that PAQR3 expression was lower in GCA tissues, HGC27, and SGC7901 cells. PAQR3 can inhibit the proliferation, migration, and invasion of HGC27 cells. Mechanistically, PAQR3 was able to inhibit the epithelial–mesenchymal transition (EMT) process in HGC27 cells through regulating TGF‐β/Smad signaling.